Model of sociolinguistic forecasting and the current trends of language policy in the regions of Russia - Bitkeeva, Aysa N. (The New Research of Tuva, 2022)
The article deals with the issues of the concept and methodology of sociolinguistic prognosis in a multiethnic state. The author presents possible scenarios for the development of language policy in the Russian Federation at the federal and regional levels. The article uses data from a sociolinguistic survey as an empirical material. It was conducted in 2021 in the Republic of Tuva, the Republic of Dagestan, the Republic of Kalmykia and Primorsky Krai.In recent decades, there have been changes in the world and Russia in relation to linguistic diversity and the principles of language policy-making. The need to develop a new language policy in Russia that would reflect the interests of the state and its citizens has become realized. The strategic application of sociolinguistic predictive models in language policy increases the efficiency of its measures. The basis for the scenario method in sociolinguistics consists in creating a multifactorial scenario model that includes typological aspects of language policy.When choosing regions to study, the author and her colleagues described the whole set of linguistic communities in Russia according to the following development models: stable type of language development (Russian), promising type of development (Chechen, Tatar, Yakut, Tuvan, etc.), unstable type of language development (Kalmyk, Karelian, Dagestan languages), and unpromising type of development (the Taz language, etc.). The analysis of the state and prospects of language development in the surveyed regions within the framework of a multicomponent prognostic model was based on correlating factors. This allowed to conclude that the best possible scenario of language policy in Russia is a multilingual liberal language policy. Its essence lies in the fact that minority and majority peoples of the country study in their native languages, simultaneously mastering the national language — Russian, regional and foreign languages through the field of education. The development of such language policy tools is a priority goal for contemporary Russia.
Keywords: languages of Russia; language policy; sociolinguistic prognosis; method of language development scenario; language death; Tuvan language; Republic of Tuva; Kalmyk language; Republic of Kalmykia; languages of Dagestan; Republic of Dagestan; Taz people; Primorsky Krai